Analysis of the Chondroitinase Operon of Flavobacterium Columnare - Sorlien, Erin L (DigitalCommons@URI, 2013)
Analysis of the chondroitinase operon of Flavobacterium columnare Erin Sorlien Major Cell and Molecular Biology, Chemistry Advisor Dr. David R. Nelson Date May 2, 2013 Keywords Flavobacterium columnare, columnaris disease, chondroitin AC lyase, complementation, csl operon Abstract Flavobacterium columnare, an opportunistic bacterial pathogen of fish, is the causative agent of columnaris disease (CD). The bacterium is a Gram-negative rod that exhibits gliding motility and avidly forms biofilms. CD affects both wild and cultured freshwater fish, and continues to cause large economic losses to the fish farming industry. According to an investigation conducted by the National Animal Health Monitoring System, CD caused losses of food-size fish in 39.0% of the US channel catfish operations, establishing CD as the most prevalent disease among catfish farms in 2010. Estimates of mortality of the disease vary significantly; however, it is clear the disease is of great economic importance. Infections have been reported in other cultured fish including tilapia, Atlantic salmon, Arctic char and rainbow trout. The disease presents as lesions on the exterior of the fish, specifically on the fins, gills and body surface. Virulence factors proposed in F. columnare include the ability to adhere to surfaces, extracellular proteases, and chondroitin AC lyase. The evidence for the role of these proposed virulence factors is primarily based on the clinical signs of the disease and is merely suggestive. During CD outbreaks bacterial isolates have been collected from moribund fish that do not exhibit the characteristic external lesions. Characterization of the genetic basis of the virulence of this important pathogen is key to describing and accurately understanding how F. columnare generates infection in the host. The specific virulence mechanisms that this bacterium uses to infect its host are not well studied or understood. Chondroitin AC lyase (chondroitinase) is one of the proposed virulence factors that may enhance the invasion ...